Paixões, pecados, picardia e poesia na publicidade radiofônica - Lalinde, Felipe Alberto de Queiroz (2006)
The advertising discourse is the most present and that provokes a biggest impact in the complex and heterogenic contemporary society due to the pulse, tensions, conflicts, expectations and frustrations it generates. This study analyses the advertising discourse in radio ads and offers a panorama of the manipulation strategies used in its texts, hoping to give its contribution to communication students and creative professionals on finding their clues to overcome the proper limits of this medium, once that this is an easier task to make when one can count on visual resources of image media. The radio has some syncretic characteristics given by verbal, vocal, musical and other sound effect resources. These resources take part of the advertising narrative, passionate, figurative and enunciative tracks. Besides promoting the product brand and inform about its benefits, the ads also tries to satisfy the consumers latent and secret desires. These desires manifest human passions. The realization of individual passions sometimes requires the transgression of moral and legal values of a particular society in a particular era. As to distinguish and differentiate itself from the advertising universe, the advertising discourse has to astonish, and almost always does it, inciting us to break with these values. This research investigated on how does radio spots and jingles explore the modalization of human passions, becoming into transgression invitations. When the moral values are also precepts of a religion tradition, its broken are considered sins. Semiotics is one of the most developed and more advanced theory and methodology dominium into the language and signification sciences environment. This was the methodology that based the research of sense production process, the manipulation mechanisms, and the efficacy of the expression resources presented in this work. The chosen corpus is compound of nine jingles and spots of food products and restoration services. The analysis of its elements, using resources of verbal, vocal, musical and sound effects demonstrated that they participate on the sense construction and are oriented to the affection and modalization of human passions. As passions are liable to the sanctions of moralization, by the absence or by the excess, in a general mode the achieved results demonstrated the presence of transgression incitation. In the particular case of moral values dictated by the Christian-catholic tradition, in minor or larger grade, the presence of a Sin invitation was evidenced